Effects of Tranexamic Acid on Hemorrhage Control and Deep Venous Thrombosis Rate After Total Knee Arthroplasty: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Ling, Tao; Zhao, Zhihu; Xu, Wenwen; Ge, Weihong; Huang, Lingli (Frontiers in Pharmacology, 2021)
Background: Total knee arthroplasty (TKA) surgery has a lot of complications, especially hemorrhage, which can be controlled via tranexamic acid (TXA). The guidelines endorse the integration of TXA interventions in the management of TKA-induced complications. However, uncertainty surrounds the effects of different TXA therapies. This frequentist model network meta-analysis (NMA) aims to compare hemorrhage control and deep venous thrombosis (DVT) rate of different TXA therapies in TKA. Methods: Articles were searched with the PubMed, Embase, Cochrane Library, and Web of Science from 1966 to October 2020. Randomized controlled trials (RCTs) comparing different TXA therapies, or with placebo in patients with TKA were included. Two investigators independently conducted article retrievals and data collection. The outcome was total blood loss and DVT rate. Effect size measures were mean differences (MDs), or odds ratios (ORs) with 95% confidence intervals (CIs). We conducted a random-effects NMA using a frequentist approach to estimate relative effects for all comparisons and rank treatments according to the mean rank and surface under the cumulative ranking curve values. All analyses were performed in Stata software or R software. The study protocol was registered with PROSPERO, number CRD42020202404. Results: We identified 1 754 citations and included 81 studies with data for 9 987 patients with TKA. Overall, all TXA therapies were superior to placebo for total blood loss in TKA. Of all TXA therapies, M therapy (IV/IV infusion + oral TXA > 3g) was most effective for total blood loss (MD=−688.48, −1084.04–−328.93), followed by F therapy (IV TXA ≥ 15 mg/kg or 1 g three times). TXA therapies in this study are not associated with the increase of DVT risk. Conclusions: TXA therapies in this study are effective and safe for the treatment of TKA-induced complications. M therapy (IV/IV infusion + oral TXA > 3 g) may be the most effective TXA therapy for hemorrhage control. TXA therapies in this study do not increase DVT risk. Considering hemorrhage control and DVT rate simultaneously, F therapy (IV TXA ≥ 15 mg/kg or 1 g three times) may be suggested to apply for TKA, and this study may provide a crucial clue to future TXA use.